STRATEGI PENGEMBANGAN MASYARAKAT ISLAM DALAM MENINGKATKAN PARTISIPASI MASYARAKAT TERHADAP POTENSI DESA - Syamsul Arifin; Ainur Rofiq (AT TAMKIN : Jurnal Pengembangan Masyarakat Islam dan Perubahan Sosial, 2022)
Designing a change plan then what is needed is the conformity between the plan that we do in accordance with the state of society. This study uses normative juridical research to find the truth of coherence, namely how the strategy of developing Islamic communities in increasing community participation in the potential of the village. Furthermore, this research, literature (library research). The approach used in this research is a qualitative approach that is often called a naturalistic research method because the research is carried out in natural conditions (natural setting). Research materials use primers that are authoritative while skunder materials are publications that include books and journals. The results of the study that with the participation of the community as a form of empowerment of local communities which certainly provides opportunities and opportunities for the community to participate and be involved in developing the potential of the village to be more effective and efficient to achieve the desired goals and feel they have and be responsible. Stratigi used first, the Growth strategy. Second, the Welfare Strategy. Third, the Responsitive strategy. Fourth, the integrated or holistic strategy.